2010
DOI: 10.1021/bi101254p
|View full text |Cite
|
Sign up to set email alerts
|

Functional Importance of Tyrosine 294 and the Catalytic Selectivity for the Bis-Fe(IV) State of MauG Revealed by Replacement of This Axial Heme Ligand with Histidine,

Abstract: The diheme enzyme MauG catalyzes the posttranslational modification of a precursor protein of methylamine dehydrogenase (preMADH) to complete the biosynthesis of its protein-derived tryptophan tryptophylquinone (TTQ) cofactor. It catalyzes three sequential two-electron oxidation reactions which proceed through a high valent bis-Fe(IV) redox state. Tyr294, the unusual distal axial ligand of one c-type heme, was mutated to His and the crystal structure of Y294H MauG in complex with preMADH reveals that this heme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(88 citation statements)
references
References 55 publications
8
80
0
Order By: Relevance
“…3 E and F). Although this additional absorbance feature is weak, its appearance is consistent with the presence of compound I (18)(19)(20)(21). A similar change in kinetic mechanisms was observed when monitoring the reaction in the NIR region.…”
Section: Resultssupporting
confidence: 74%
“…3 E and F). Although this additional absorbance feature is weak, its appearance is consistent with the presence of compound I (18)(19)(20)(21). A similar change in kinetic mechanisms was observed when monitoring the reaction in the NIR region.…”
Section: Resultssupporting
confidence: 74%
“…2A). These spectral changes were more pronounced with the optimized 10:1 ratio of H 2 O 2 than with the stoichiometric ratio used in prior studies (15,16), consistent with a more complete formation of the bis-Fe(IV) species. The absorption maxima for the newly developed Q-bands are similar to those observed in ferryl species from nonglobin peroxidases, such as cytochrome c peroxidase (21) and horseradish peroxidase (22), but are different from those reported for ferryl species from globins (540-545 and 580-590 nm) (23).…”
Section: Resultssupporting
confidence: 69%
“…The NIR region of the electronic absorption spectrum of the bis-Fe (IV) species was not explored in previous studies (13,15,16). Inspection of this region revealed that a broad band centered at 950 nm developed upon addition of H 2 O 2 to diferric MauG concomitant with the previously observed changes in the visible region of the spectrum ( Fig.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations